2005
DOI: 10.1071/rdv17n2ab94
|View full text |Cite
|
Sign up to set email alerts
|

94 COMPARING DIFFERENT LEVELS OF OSMOLARITY AND pH OF LACTOSE EXTENDER ON THE VIABILITY OF SPERMATOZOA IN THE BACTRIAN CAMEL (CAMELUS BACTRIANUS)

Abstract: The objective of this study was to determine the effects of genetic manipulation, cell type, and culture conditions on developmental potential of bovine nuclear transfer (NT) embryos. Ovum pickup (OPU) technology was developed to obtain the oocytes for NT. A total 4044 cumulus-oocyte complexes (COCs) were obtained during 492 OPU sessions, with an average of 8.2 COCs recovered each session. Cultured granulosa cells (CGC), bovine fetal (150 days) oviduct epidermic cells (FOEC), and adult ear skin fibroblasts (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In another study using a lactose-based extender, the post-thaw motility of 35% was reported in Dromedary camel [41]. We have found that progressive forward motility of Bactrian camel sperm was adversely affected when the semen was extended in lactose or sucrose extenders [5,[42][43][44]. Therefore, we decided not to use these extenders in our further studies.…”
Section: Discussionmentioning
confidence: 80%
“…In another study using a lactose-based extender, the post-thaw motility of 35% was reported in Dromedary camel [41]. We have found that progressive forward motility of Bactrian camel sperm was adversely affected when the semen was extended in lactose or sucrose extenders [5,[42][43][44]. Therefore, we decided not to use these extenders in our further studies.…”
Section: Discussionmentioning
confidence: 80%